Venous thromboembolism diagnosis: unresolved issues - Righini, Marc; Le Gal, Grégoire; Bounameaux, Henri (Thrombosis and Haemostasis, 2015)
Recent advances in the management of patients with suspected VTE have both improved diagnostic accuracy and made management algorithms safer, easier to use and well standardised. These diagnostic algorithms are mainly based on the assessment of clinical pretest probability, D-dimer measurement and imaging tests, mainly represented by compression ultrasound (CUS) for suspected DVT and computed tomography pulmonary angiography (CTPA) or lung ventilationperfusion scan for pulmonary embolism. These diagnostic algorithms allow a safe and cost-effective diagnosis for most patients with suspected VTE. In this review, we focus on the challenge of diagnosing VTE in special patient populations, such as elderly patients, pregnant women, or patients with a prior VTE. Some additional challenges are arising that might require adjustments to current diagnostic strategies, such as the reduced clinical suspicion threshold, resulting in a lower proportion of VTE among suspected patients; the overdiagnosis and overtreatment of VTE, especially regarding calf deep-vein thrombosis (DVT) and subsegmental pulmonary embolism (SSPE).
Keywords: Deep vein thrombosis; pulmonary embolism; D-dimer; age-adjusted D-dimer; compression ultrasonography; computed tomography pulmonary angiography